CCN3, a key matricellular protein, distinctly inhibits TGFÎ²1-mediated Smad1/5/8 signalling in human podocyte culture - Madne, Tarunkumar Hemraj; Dockrell, Mark Edward Carl (Cellular and Molecular Biology, 2018)
Growth factors like TGFÎ² and CTGF (CCN2) plays a vital role in various cellular functions. TGFÎ² and CTGF are overexpressed in renal fibrosis. CTGF act as profibrotic stimuli to TGFÎ². CCN3 is a member of CCN family which also comprises CCN1 (CYR61), CCN2 (CTGF), CCN4 (WISP-1), CCN5 (WISP-2) and CCN6 (WISP-3). CCN3 has been shown to antagonise CTGF. In this study, we investigated the role of CCN3 in TGFÎ²1-mediated signalling in human podocytes culture. This study describes the novel function of CCN3 in regulation of TGFÎ²1 mediated non-canonical Smad signalling in human podocytes culture. Experiments were conducted on conditionally immortalised human podocytes incubated with TGFÎ²1 (1.25ng/ml and 2.5ng/ml) and CCN3 (360ng/ml). Western blot study was performed to study signalling proteins. RT-PCR was performed to study alternative splicing of Fibronectin (Fn). Real time PCR was performed to look for gene expression of Fn and collagen IV and collagen I. TGFÎ²1 induced the Smad1/5/8, Smad3 and p38 phosphorylation and CCN3 downregulated the TGFÎ²1 induced Smad1/5/8 phosphorylation and did not affect Smad3 and p38 phosphorylation. In addition to this CCN3 induced alternative splicing of Extra domain A Fibronectin (EDA+Fn). CCN3 also induced collagen IV, Collagen I and Fn gene expression. This is the first evidence of downregulation of TGFÎ²-mediated activation of a Smad1/5/8 signalling pathway by CCN3 in human podocytes and in any cell type. Targeting CCN3-mediated events could provide exciting outcomes in the understanding of molecular mechanism of fibrosis.